New Class of Efficient Terahertz Generators: Effective Terahertz Spectral Filling by Complementary Tandem Configuration of Nonlinear Organic Crystals - Kang, Bong Joo; Lee, Seung Heon; Kim, Won Tae; Lee, Seung Chul; Lee, Kanghee; Benacchio, Giordano; Montemezzani, Germano; Jazbinsek, Mojca; Kwon, O. Pil; Rotermund, Fabian (Advanced Functional Materials, 2018)
Intense table-top terahertz (THz) sources, which have progressed tremendously in the last decade, are becoming more important for advanced THz science to study light–matter interactions and subsequent applications. Nonlinear optical organic crystals exhibit great potential for intense broadband THz wave generation due to their large nonlinearities and advantageous phase-matching characteristics. However, the phonon-induced absorption of most organic crystals in the THz region leads to undesired modulation of the spectrum and limits the THz output efficiency. To overcome such drawbacks, phonon-mode engineering by modification of molecular structures is suggested, but intrinsic limitations still remain. Here, an efficient alternative approach has been recently proposed for generating intense broadband THz waves based on a tandem configuration that combines two complementary nonlinear organic crystals. Such configuration compensates for the spectral gap of the generated THz waves mainly caused by phonon absorption and additionally enhances the optical-to-THz conversion efficiency. The proposed organic tandem generator indicates a substantial enhancement of the peak-to-peak THz electric field due to effective spectral filling at phonon absorption gaps. As a result, such tandem configuration provides a versatile platform to generate gapless broadband THz spectra with suppressed phonon absorption and contributes to advancing the development of intense broadband coherent THz sources.
Keywords: Electrooptic crystals; Induced absorption; Light-matter interactions; Non-linear optical; Organic crystal; Phonon absorption; Spectral gap; Tandem configuration; electro-optic crystals; nonlinear optics; organic crystals; terahertz waves